Storyboard design course : principles, practice, and techniques : the ultimate guide for artists, directors, producers, and scriptwriters - Cristiano, Giuseppe (Hauppauge, NY : Barron's, 2007)
A course in storyboard design for media productions, featuring forty lessons covering types of storyboards, workspaces, materials and equipment, drawing skills, requirements for different types of storyboards, fluidity, the various forms from which a storyboard artist works, working methods, and professional practice.
"A Quarto book"--T.p. verso.
Includes bibliographical references (p. 182-183) and index.
Adult
Keywords: Commercial art -- Technique; Storyboards; Commercial art -- Technique; Storyboards